Impact on optical image quality from glistenings in intraocular lenses - preliminary study - Geniusz, Maliwna; Kazimierska, Marta; Zając, Marek (Photonics Letters of Poland, 2015)
<!-- saved from url=(0022)http://internet.e-mail --> The aim of the study was to determine how glistenings phenomenon affects the quality of the retinal image. A long presence of the artificial intraocular lens (IOL) inside the eye causes that different defects appear in lens implant. In particular the appearance of liquid-filled microvacuoles inside a lens is known as glistenings. These changes affect the imaging properties of the lens and hence the influences the quality of the retinal image. As a result of imaging deterioration significant worsening of the eyesight may occur. Such defects occurs in all types of IOLs and are quite common. In this paper numerical investigation of imaging quality of IOLs with glistening is presented. Three intraocular lenses were examined in the study, two made of acrylic and one made of PMMA. The Atchison eye model was adopted for calculations. Microvacuoles were modelled in different size and density. This paper shows the dependence of the retinal image quality and the parameters above. The results proved that the degree of deterioration in the image quality in IOLs with microvacuoles of the same size and density differs for each IOL type of different construction parameters. Full Text: PDF References A. Miyata et al., "Clinical and Experimental Observation of Glistening in Acrylic Intraocular Lenses", Jap. J. Opht. 45, 564 (2001). CrossRef H. Matsushima et al., "Analysis of surface whitening of extracted hydrophobic acrylic intraocular lenses", J. Cataract. Refr. Surg. 35, 1927 (2009). CrossRef M. Nagata et al., "Clinical evaluation of the transparency of hydrophobic acrylic intraocular lens optics", J. Cataract. Refr. Surg. 36, 2056 (2010). CrossRef R. Mackool, J. Colin, "Limitations of Scheimpflug photography in quantifying glistenings", J. Cataract. Refr. Surg. 35, 1480 (2009). CrossRef D. Saylor et al., "Osmotic cavitation of elastomeric intraocular lenses", Acta Biomater 6, 1090 (2010). CrossRef O. Omar et al., "In vitro analysis of AcrySof intraocular lens glistenings in AcryPak and Wagon Wheel packaging", J. Cataract. Refr. Surg. 24, 107 (1998). CrossRef E. Mönestam, A. Behndig, "Impact on visual function from light scattering and glistenings in intraocular lenses, a long-term study", Acta Ophtalmol. 89, 724 (2011). CrossRef K. Kato et al., "Glistening formation in an AcrySof lens initiated by spinodal decompositionof the polymer network bytemperature change", J. Cataract. Refr. Surg. 27, 1493 (2001). CrossRef J. Colin, I. Orignac, D. Touboul, "Glistenings in a large series of hydrophobic acrylic intraocular lenses", J. Cataract. Refr. Surg. 35, 2121 (2009). CrossRef H. Dick et al., "Vacuoles in the AcrysofTM Intraocular Lens as Factor of the Presence of Serum in Aqueous Humor", Ophtalmic Res. 33, 61 (2001). CrossRef M. Ayaki et al., "Surfactant Induced Glistenings: Surface Active Ingredients in Ophthalmic Solutions May Enhance Water Entry into the Voids of Implanted Acrylic Intraocular Lenses", J Long-Term Eff. Med. 16, 451 (2006). CrossRef M. Ronbeck et al., "Comparison of glistenings in intraocular lenses with three different materials: 12-year follow-up", Acta Ophtalmol. 91, 66 (2013). CrossRef D.J. Apple et al., "Snowflake degeneration of polymethyl methacrylate posterior chamber intraocular lens optic material", Ophtalmology 109, 1666 (2002). CrossRef N. Dahle et al., "Localized, Central Optic Snowflake Degeneration of a Polymethyl Methacrylate Intraocular Lens: Clinical Report With Pathological Correlation", JAMA Ophtalmol. 124, 1350 (2006). CrossRef D.A. Atchison, "Optical models for human myopic eyes", Vision Research 46, 2236 (2006). CrossRef E. DeHoog, A. Doraiswamy, "Evaluation of the impact of light scatter from glistenings in pseudophakic eyes", J. Cataract. Refr. Surg. 40, 95 (2014). CrossRef T. Oshika et al., "Influence of glistenings on the optical quality of acrylic foldable intraocular lens", Br. J. Ophthalmol. 85, 1034 (2001). CrossRef